Maximizing Common Bean (Phaseolus vulgaris L.) Productivity Through Application of Organic and Inorganic Fertilizers in Alkaline Soil - Safiullah Habibi; Shafiqullah Aryan; Ali Yawar Seerat; Kalimullah Saighani; Mohammad Daud Haidari (Applied Biosciences)
Common beans are a vital source of protein, vitamins, and minerals. Increasing common beans productivity is crucial for improving food security and farmers’ incomes globally. This study evaluated the growth and yield responses of common beans to integrated organic and inorganic fertilizers under field conditions at the Faculty of Agriculture, Kabul University. The trial was repeated over two consecutive growing seasons in 2020 and 2021, using a randomized complete block design with 18 treatments and three replications. The fertilizers used included urea (N) (0, 60, and 90 kg/ha), diammonium phosphate (D) (0, 50, and 100 kg/ha), and farmyard manure (O) (0 and 5000 kg/ha). The results show that integrated fertilizers, particularly O5000N60D50, O5000N60D100, O5000N90D50, and O5000N90D100, significantly increased growth and yield parameters. In 2020, the grain yield increased significantly (p < 0.05) by 75.6, 76.7, and 68.4% with the O5000N60D50, O5000N60D100, and O5000N90D100 treatments, respectively. In 2021, O5000N60D50, O5000N60D100, and O5000N90D50 showed significant yield increases of 94.7, 89.6, and 97.9%, respectively. The grain yield strongly correlated with the SPAD value (r = 0.84), number of pods per plant (r = 0.71), and number of seeds per pod (r = 0.66) in 2020, and it more strongly correlated with the SPAD value (r = 0.91), number of pods per plant (r = 0.77), and number of seeds per pod (r = 0.76) in 2021. A principal component analysis highlighted the effectiveness of organic–inorganic fertilizer combinations, particularly O5000N60D50, in enhancing productivity while potentially reducing inorganic fertilizer application. This study demonstrates that integrating organic and inorganic fertilizers enhances sustainable crop productivity and reduces negative environmental impacts, particularly in regions facing nutrient depletion and drought conditions.